Step
*
1
4
of Lemma
bag-drop-commutes
1. T : Type
2. eq : EqDecider(T)
3. bs : bag(T)
4. x : T
5. y : T
6. ∀x,y:T.  Dec(x = y ∈ T)
7. ¬(x = y ∈ T)
8. ∀x:T. ∀bs:bag(T).
     ((∃as:bag(T). ((bs = ({x} + as) ∈ bag(T)) ∧ (bag-remove1(eq;bs;x) = (inl as) ∈ (bag(T)?))))
     ∨ ((¬x ↓∈ bs) ∧ (bag-remove1(eq;bs;x) = (inr ⋅ ) ∈ (bag(T)?))))
9. as : bag(T)
10. bs = ({x} + as) ∈ bag(T)
11. bag-remove1(eq;bs;x) = (inl as) ∈ (bag(T)?)
12. a1 : bag(T)
13. bs = ({y} + a1) ∈ bag(T)
14. bag-remove1(eq;bs;y) = (inl a1) ∈ (bag(T)?)
15. ¬y ↓∈ as
16. bag-remove1(eq;as;y) = (inr ⋅ ) ∈ (bag(T)?)
17. ¬x ↓∈ a1
18. bag-remove1(eq;a1;x) = (inr ⋅ ) ∈ (bag(T)?)
⊢ as = a1 ∈ bag(T)
BY
{ (Assert x ↓∈ bs BY
         OnMaybeHyp 10 (\h. (HypSubst h 0
                             THEN Auto
                             THEN ((BLemma `bag-member-append`  THENM D 0)
                                   THEN Auto
                                   THEN OrLeft
                                   THEN Auto
                                   THEN BLemma `bag-member-single`
                                   THEN Auto)⋅))) }
1
1. T : Type
2. eq : EqDecider(T)
3. bs : bag(T)
4. x : T
5. y : T
6. ∀x,y:T.  Dec(x = y ∈ T)
7. ¬(x = y ∈ T)
8. ∀x:T. ∀bs:bag(T).
     ((∃as:bag(T). ((bs = ({x} + as) ∈ bag(T)) ∧ (bag-remove1(eq;bs;x) = (inl as) ∈ (bag(T)?))))
     ∨ ((¬x ↓∈ bs) ∧ (bag-remove1(eq;bs;x) = (inr ⋅ ) ∈ (bag(T)?))))
9. as : bag(T)
10. bs = ({x} + as) ∈ bag(T)
11. bag-remove1(eq;bs;x) = (inl as) ∈ (bag(T)?)
12. a1 : bag(T)
13. bs = ({y} + a1) ∈ bag(T)
14. bag-remove1(eq;bs;y) = (inl a1) ∈ (bag(T)?)
15. ¬y ↓∈ as
16. bag-remove1(eq;as;y) = (inr ⋅ ) ∈ (bag(T)?)
17. ¬x ↓∈ a1
18. bag-remove1(eq;a1;x) = (inr ⋅ ) ∈ (bag(T)?)
19. x ↓∈ bs
⊢ as = a1 ∈ bag(T)
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  bs  :  bag(T)
4.  x  :  T
5.  y  :  T
6.  \mforall{}x,y:T.    Dec(x  =  y)
7.  \mneg{}(x  =  y)
8.  \mforall{}x:T.  \mforall{}bs:bag(T).
          ((\mexists{}as:bag(T).  ((bs  =  (\{x\}  +  as))  \mwedge{}  (bag-remove1(eq;bs;x)  =  (inl  as))))
          \mvee{}  ((\mneg{}x  \mdownarrow{}\mmember{}  bs)  \mwedge{}  (bag-remove1(eq;bs;x)  =  (inr  \mcdot{}  ))))
9.  as  :  bag(T)
10.  bs  =  (\{x\}  +  as)
11.  bag-remove1(eq;bs;x)  =  (inl  as)
12.  a1  :  bag(T)
13.  bs  =  (\{y\}  +  a1)
14.  bag-remove1(eq;bs;y)  =  (inl  a1)
15.  \mneg{}y  \mdownarrow{}\mmember{}  as
16.  bag-remove1(eq;as;y)  =  (inr  \mcdot{}  )
17.  \mneg{}x  \mdownarrow{}\mmember{}  a1
18.  bag-remove1(eq;a1;x)  =  (inr  \mcdot{}  )
\mvdash{}  as  =  a1
By
Latex:
(Assert  x  \mdownarrow{}\mmember{}  bs  BY
              OnMaybeHyp  10  (\mbackslash{}h.  (HypSubst  h  0
                                                      THEN  Auto
                                                      THEN  ((BLemma  `bag-member-append`    THENM  D  0)
                                                                  THEN  Auto
                                                                  THEN  OrLeft
                                                                  THEN  Auto
                                                                  THEN  BLemma  `bag-member-single`
                                                                  THEN  Auto)\mcdot{})))
Home
Index